Kecerdasan Emosional Memoderasi Pengaruh Tekanan Peran terhadap Kejenuhan Kerja Auditor Pada KAP Provinsi Bali - Antari, Ni Putu Yulia; Alit Suardana, Ketut (E-Jurnal Akuntansi, 2021)
The purpose of this study is to analyze emotional intelligence moderating the influence of role pressure on the saturation of auditor performance in Bali Provincial Public Accountant Firm. This research was conducted in all Public Accountant Firm offices in Bali Province as many as nine offices in the Bali Region in 2019 by making 48 auditors as samples with the saturated sample method. Data collection is done by distributing questionnaires, tested through regression analysis moderation techniques. Based on the results of the analysis, the role pressure variable has a significant positive effect on the saturation of the auditor's performance at Public Accountant Firm in Bali Province. Emotional intelligence moderates the influence of role pressure significantly positive effect on the saturation of the auditor's performance on Public Accountant Firm in the province of Bali. Keywords: Role Pressure; Emotional Intelligence; Work Saturation.